ACCP-negative rheumatoid arthritis – clinical and immunological features - D. A. Dibrov (Научно-практическая ревматология, 2022)
Depending on the presence of laboratory biomarkers: rheumatoid factor IgM and anti-cyclic citrullinated peptide antibodies (ACCP), “seropositive” and “seronegative” variants of rheumatoid arthritis (RA) are distinguished. Immunological subtypes differ in risk factors, immunopathogenesis, and the course of the disease. A review of data concerning immunology and clinical features of ACCP-negative rheumatoid arthritis is presented. The presence of ACCP in the peripheral blood reflects the progressive erosive process with a predominance of the inflammatory component and involvement of the B cells. Proliferative changes predominate in the ACCPnegative subtype; disorders associated with the T-cell link, primarily with CD4+ T-lymphocytes, play an important role in pathogenesis. This variant of the disease is characterized by a less pronounced erosive process, but the inflammatory activity in both subtypes of RA can be comparable. Early diagnosis, regular monitoring of the disease activity and the «treat to target» strategy are recommended for both positive and negative ACCP RA, however, the effectiveness of individual drugs in these subtypes may vary significantly.